2014
DOI: 10.1007/s11882-014-0498-5
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Immunotherapy in the Treatment of Atopic Dermatitis: a Systematic Review Using the GRADE System

Abstract: Controversy exists regarding the role of allergen immunotherapy as a therapeutic intervention for patients with atopic dermatitis and aeroallergen sensitivity. Our aim was to critically appraise the evidence supporting the use of sublingual immunotherapy for patients with atopic dermatitis and aeroallergen sensitivity. We performed a literature search using the terms "sublingual immunotherapy" and "atopic dermatitis" and "sublingual immunotherapy" and "eczema." We used the same terms to search PubMed, Ovid, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…14 No serious adverse reactions occurred in our SLIT group or control groups. There were no life-threatening adverse reactions or fatalities over 3 years, similar to the results of other clinical studies, 11,12,14 suggesting that SLIT is safe for the treatment of pediatric AD.…”
Section: Discussionsupporting
confidence: 85%
“…14 No serious adverse reactions occurred in our SLIT group or control groups. There were no life-threatening adverse reactions or fatalities over 3 years, similar to the results of other clinical studies, 11,12,14 suggesting that SLIT is safe for the treatment of pediatric AD.…”
Section: Discussionsupporting
confidence: 85%
“…[112][113][114][115] The studies consistently show that a desensitization can be achieved in a proportion of children, but it is not clear if a permanent tolerance can be induced, and the high rate of side effects has also to be considered. Under a more general perspective, favourable reports with epicutaneous immunotherapy in food allergy are now available, but the results are still not conclusive 116 The results are more controversial with SLIT for atopic dermatitis, 117,118 although this field remains an intriguing opportunity. A summary of the possible developments of SLIT and AIT in general, is summarized in Figure 4.…”
Section: Pre S Ent Future and Unme T Needs Of S Litmentioning
confidence: 99%
“…Those studies involved various antigens, methods of administration, study durations, and outcome measures. Four systematic reviews have evaluated the results of ASIT studies, and those also generated different conclusions 74 75 76 77 . A recent Cochrane review concluded that there is limited evidence to support the view that ASIT benefits patients with AD due to the paucity of trials and participants, wide confidence intervals, extensive loss to follow-up, and lack of blinding in some studies 77 .…”
Section: Resultsmentioning
confidence: 99%